Rising Patriarchy and Declining Economic Opportunity: Life Courses and Social Change in Egypt between 1965 and 2018 - Zafer Buyukkececi; Anette Eva Fasang; Vered Kraus (Population and Development Review, 2023)
Despite Egypt's economic growth and educational expansion, gender inequalities and a lack of economic opportunities for young adults persist. Existing studies on social change in Egypt often rely on aggregate trend indicators or focus on isolated point-in-time work or family outcomes. This study adopts a life course perspective to (1) trace cohort changes in work-family life courses for individuals born between 1956 and 1988 (N = 19,970) from 1965 to 2018, (2) assess gender inequality trends in life courses across cohorts, and (3) link different life course patterns to aggregate development indicators. Using retrospective data from the Egyptian Labor Market Panel, multichannel sequence and cluster analyses identify ten typical life course profiles that can be divided into: a state-structured life course; and various manifestations of family- and market-structured life courses. The economically secure state-structured life course declined in favor of rising market-structured and family-structured life courses. Gender inequality in employment increased across cohorts. GDP growth was associated with economically insecure market-structured life courses for men and family-structured life courses of economic inactivity for women. Cohort change in life courses was most rapid in the transition period from authoritarian socialism to unregulated crony capitalism (1980–1990) when cohorts born in the 1970s reached adulthood.
Keywords: 300; life course; young adulthood; work; family; gender; MENA; sequence analysis